#TITLE_ALTERNATIVE# - HARIYADI (NIM : 12308059), WISNU
One of disadvantage in gravity measurement on surface is insufficient in vertical resolution. Borehole gravity method is done by measuring gravity response in certain depth interval inside a borehole to acquire better information of layer thickness caused by density contrast. Forward modeling with synthetic models is made to identify characteristics of borehole vertical gradient response and borehole second vertical derivative (SVD) anomaly. These characteristics will be applied on real data from observation fields to determine subsurface layer and its density contrast type, in addition to estimate rock formation’s density and porosity. Results show that borehole SVD anomaly can determine subsurface layer and its density contrast type better than borehole vertical gradient response. Besides that, borehole gravity data can be used to estimate rock formation’s density and porosity, with average error value of 1,72% for interval density data to density log and 7,76% for interval porosity data to porosity log.